Influence of factor application between utilizing modified united theory of acceptance and use of the technology 2 model (a study on Shopee users in Indonesia) - Rissella Jihan Syanita; Indrawati Indrawati; Astri Ghina (Institute of Computer Science (IOCS), 2023)
The internet has become a part of people's daily lives to help them fulfil their needs, such as enabling them to trade or do business utilizing e-commerce applications. Shopee is one of the most well-liked e-commerce platforms in Indonesia, boasting 93 million active users. This study used the modified UTAUT 2 model to conduct a descriptive analysis to identify the application user assessment. Subsequently, the SEM PLS analysis was conducted to identify variables influencing the continuation intention of application usage and the impact of the continuation intention on the user behavior of Shopee application users. The study also sought to ascertain the impact of age and gender on the other variables in the study model. As a result, the business can identify user preferences and factors that affect how often users use the Shopee program, enabling it to maintain its appeal in the face of strong competition. The study findings revealed that social influence, perceived security, and risk received lower ratings than other categories. In conclusion, the intention of application users to continue using it was highly influenced by performance expectations, effort expectations, social influence, enabling conditions, headache incentives, habit, and perceived security and risk.